Urgent Right Hemicolectomy - S. N. Shchayeva (Неотложная медицинская помощь, 2022)
Abstract Right hemicolectomy with the formation of primary ileotransverse anastomosis is the method of choice in emergency surgery as well.Aim of the study Comparative evaluation of the results of urgent right hemicolectomy with the formation of a primary anastomosis and without the formation of a primary anastomosis at the first stage of surgical intervention.Material and methods A retrospective cohort study included patients who underwent emergency right hemicolectomy. The database includes: demographic indicators, comorbidity, data on the general condition of the patient, the time of the surgical intervention, the time from the onset of the disease to hospitalization, laboratory parameters. The patients were divided into two groups. Group 1 included patients in whom the operation was performed with the formation of a primary anastomosis, which was applied manually; group 2 consisted of patients who underwent surgery with the formation of a separate double-barrel stoma and the 2nd stage of surgical intervention was planned. The Clavien–Dindo classification was used to assess postoperative complications.Results The results of 112 right hemicolectomies performed according to emergency indications were analyzed. Group 1 (operations with the formation of a primary anastomosis) included 87 patients (77.7%); group 2 (n=25) included 18 patients (16.1%) who underwent two-stage operations: stage 1 — right hemicolectomy without primary anastomosis formation, stage 2 — restorative intervention, anastomosis formation; and 7 patients (6.2%), in whom the operation ended with the formation of a separate double-barreled intestinal stoma. In the 1st group, the patients were younger: the average age was 61 years versus 73 years in the 2nd group (p=0.021). Patients of the 2nd group were in a more serious condition upon admission (ASA III–IV) and had a higher comorbidity. The average duration of surgical intervention was 162±10.2 minutes in group 1 and 110±9.5 minutes in group 2 (p=0.038). Group 2 had more serious complications (IIIB–IVB according to Clavien–Dindo) compared to group 1 (p=0.001). The main factors that had a statistically significant impact on the risk of postoperative complications were: severe degree of comorbidity (odds ratio — OR 3.1; 95% confidence interval — CI 1.4–6.3; p=0.002), severe general condition upon admission — ASA III–IV (OR 2.7; 95% CI 1.2–7.4; p=0.01), anemia — Hb<90 g/l (OR 1.7; 95% CI 1.5– 6.1; Odd=0.004), time between the onset of the disease and admission more than 12 hours (OR 2.1; 95% CI 0.9–6.8; p=0.03), time to perform the operation (OR 2 .05, 95% CI 1.38–8.1, p=0.033).Conclusion The presence of chronic diseases characterized by systemic lesions and comorbidity determines the choice of a primary treatment strategy for perforation, bleeding, acute mesenteric ischemia, where it is advisable to perform a right hemicolectomy without primary anastomosis, followed by recovery stage.